Advantages Of Using Short Stories In Enriching Lexical And Grammatical Collocations Of ESL Learners - B. Jagadeeswari; Dr.V. K. Saravanan (Revista Electronica de Veterinaria, 2024)
The main objective of ESL teaching is to help students communicate fluently in the second language. A recent trend in ESL teaching indicates the necessity of integrating literature because of its rich potential to provide an authentic model of language use. Among literary genres, short stories seem to be the most suitable choice for their potential to help students enhancing their vocabulary and also developing the four skills–listening, speaking, reading, and writing – more effectively because of the motivational benefits embedded in the stories. The purpose of this article is advantages of using short stories in enriching the lexical and grammatical collocations of ESL learners.